A Flow Microreactor Approach to a Highly Efficient Diels–Alder Reaction with an Electrogenerated o-Quinone - Tanaka, Kenta; Yoshizawa, Hirona; Atobe, Mahito (Synlett, 2019)
We have demonstrated a Diels–Alder reaction of an o-quinone generated in an electrochemical flow microreactor. In the flow microreactor system, 4-tert-butyl-o-benzoquinone was easily electrogenerated from 4-tert-butylpyrocatechol in the absence of chemical oxidants and then rapidly used, without decomposing, in a subsequent Diels–Adler reaction with various fulvenes to give the desired products efficiently.
Keywords: quinones; Diels–Alder reaction; microreactor; electrochemical synthesis; flow chemistry; butylcatechol